Physicochemical characterization by AFM, FT-IR and DSC and biological assays of a promising antileishmania delivery system loaded with a natural Brazilian product - Marquele-Oliveira, Franciane; Torres, Elina Cassia; Barud, Hernane da Silva [UNESP]; Zoccal, Karina Furlani; Faccioli, Lúcia Helena; Hori, Juliana I.; Berretta, Andresa Aparecida (Elsevier, 2016)
The control and treatment of Leishmaniasis, a neglected and infectious disease affecting approximately 12 million people worldwide, are challenging. Leishmania parasites multiply intracellularly within macrophages located in deep skin and in visceral tissues, and the currently employed treatments for this disease are subject to significant drawbacks, such as resistance and toxicity. Thus, the search for new Leishmaniasis treatments is compulsory, and Ocotea duckei Vattimo, a plant-derived product from the biodiverse Brazilian flora, may be a promising new treatment for this disease. In this regard, the aim of this work was to develop and characterize a delivery system based on solid lipid nanoparticles (SLN) that contain the liposoluble lignan fraction (LF) of Ocotea duckei Vattimo, which targets the Leishmania phagolysosome of infected macrophages. LF-loaded SLNs were obtained via the hot microemulsion method, and their physical and chemical properties were comprehensively assessed using PCS, AFM, SEM, FT-IR, DSC, HPLC, kinetic drug release studies, and biological assays. The size of the developed delivery system was 218.85 ± 14.2 nm, its zeta potential was -30 mV and its entrapment efficiency (EE%) was high (the EEs% of YAN [yangambin] and EPI-YAN [epi-yangambin] markers were 94.21 ± 0.40% and 94.20 ± 0.00%, respectively). Microscopy, FT-IR and DSC assays confirmed that the delivery system was nanosized and indicated a core-shell encapsulation model, which corroborated the measured kinetics of drug release. The total in vitro release rates of YAN and EPI-YAN in buffer (with sink conditions attained) were 29.6 ± 8.3% and 34.3 ± 8.9%, respectively, via diffusion through the cellulose acetate membrane of the SLN over a period of 4 h. After 24 h, the release rates of both markers reached approximately 45%, suggesting a sustained pattern of release. Mathematical modeling indicated that both markers, YAN and EPI-YAN, followed matrix diffusion-based release kinetics (Higuchi's model) with an estimated diffusion coefficient (D) of 1.3.10-6 cm2/s. The LF-loaded SLNs were non-toxic to murine macrophages (20-80 μg mL-1 range) and exerted a prominent anti-leishmanial effect (20 μg mL-1). These data suggest this new and well-characterized lipid nanoparticle delivery system safely and effectively kills Leishmania and warrants further clinical investigation.
Keywords: Anti-leishmanial activity; Macrophage cytotoxicity; Ocotea duckei; Solid lipid nanoparticle (SLN); Sustained drug release